Older adults' quality of life – Exploring the role of the built environment and social cohesion in community-dwelling seniors on low income. (September 2016) - Engel, L.; Chudyk, A.M.; Ashe, M.C.; McKay, H.A.; Whitehurst, D.G.T.; Bryan, S.
Abstract: The built environment and social cohesion are increasingly recognized as being associated with older adults' quality of life (QoL). However, limited research in this area still exists and the relationship has remained unexplored in the area of Metro Vancouver, Canada. This study examined the association between the built environment and social cohesion with QoL of 160 community-dwelling older adults (aged ≥ 65 years) on low income from Metro Vancouver. Cross-sectional data acquired from the Walk the Talk (WTT) study were used. Health-related QoL (HRQoL) and capability wellbeing were assessed using the EQ-5D-5L and the ICECAP-O, respectively. Measures of the environment comprised the NEWS-A (perceived built environment measure), the Street Smart Walk Score (objective built environment measure), and the SC-5PT (a measure of social cohesion). The primary analysis consists of Tobit regression models to explore the associations between environmental features and HRQoL as well as capability wellbeing. Key findings indicate that after adjusting for covariates, older adults' capability wellbeing was associated with street connectivity and social cohesion, while no statistically significant associations were found between environmental factors and HRQoL. Our results should be considered as hypothesis-generating and need confirmation in a larger longitudinal study. Highlights: Better social cohesion was associated with better capability wellbeing. Increased street connectivity was associated with lower capability wellbeing. No statistically significant associations were found for older adults' HRQoL. Our results should be considered as hypothesis-generating.